Konsekwencje migracji wysoko wykwalifikowanego kapitału ludzkiego dla krajów wysyłających i migrantów na przykładzie personelu medycznego - Agnieszka Makulec (University of Warsaw, Centre of Migration Research (CMR), 2013)
– This paper presents theoretical background for studying consequences of highly-skilled migration for individual and aggregated human capital. Contrary to the brain drain discussion, which stresses the loss for the sending countries resulting from the outflow of specialists abroad, the paper focuses on the positive impacts of migration on the countries of origin. These could be a result of acquisition of new competences (resulting in higher salaries after return), of human capital stimulation in the sending country (of both migrants and non-migrants) or of remittances sent to the country of origin. Decreased costs of highly-skilled migration due to the automatic recognition of qualifications in selected professions in the European Union (e.g. for healthcare professionals) could result in increased temporality of migration. Temporality and circularity of migration together with lack of mass migration and high transferability of experience and skills between the countries could further result in brain gain for the sending countries.
Keywords: 330; brain drain; brain gain; human capital; healthcare professionals; Brain Drain; Internationale Migration; Hochqualifizierte Arbeitskräfte; Gesundheitsberufe; Wirkungsanalyse; Humankapital